The Impact of Corporate Social Responsibility Disclosure in Terms of Quantity and Quality on the Financial Performance of Companies in Tunisia - Kalai, Lamia; Sbais, Yosr (International Review of Management and Marketing, 2019)
This article aims to study the relationship between the disclosure of CSR and the financial performance of Tunisian companies. Two measures are used to determine the CSR disclosure index: the first in terms of quantity is based on an unweighted approach from the Cooke (1991) study and the second in terms of quality is based on a system weighting of the qualitative characteristics of the information, referring to the voluntary declarations, in the annual reports of a sample of listed companies. The empirical results reveal that the amount of CSR disclosure has a positive effect on the financial performance of companies regardless of their size, their risk and debt levels, this allows us to show that the stakeholders generally give their trust to companies that have socially responsible behavior and a regular disclosure system. The results also show that the quality of CSR disclosure has a positive effect on the financial performance of companies as measured by economic, financial or stock market profitability Keywords:Social Responsibility, Financial Performance, Economic Profitability, Return on Equity JEL Classifications: G32, C12 DOI: https://doi.org/10.32479/irmm.7573